SURGICAL EQUIPMENTS FOR PEARL CULTURE - Alagarswami, K; Sivarajan, G S (Indian Journal of Fisheries, 2011)
Hie present communication describes the surgicalinstruments developed indigenously for the first time at the Surgical InstrumentsPlant. The material used in all cases is stainless steel of straight chromiumtype conforming to I.S.I, specification 30 CR 13 and 40 CR 13. The items arefabricated to fine dimensional accuracy and surface finish. Fig. 1 illustrates theinstruments developed indigenously.